Impact of universal admission testing for severe acute respiratory coronavirus 2 (SARS-CoV-2) in era of the omicron variant. (January 2023) - Williams, Victoria R.; Chan, Christina K.; Chan, Adrienne K.; Kozak, Robert; Leis, Jerome A.
Abstract: In this prospective study, universal admission testing for severe acute respiratory coronavirus virus 2 (SARS-CoV-2) averted transmission in shared patient rooms especially since the emergence of the SARS-CoV-2 omicron variant when the yield in identifying infectious asymptomatic cases more than doubled. This change may be due to the higher rate of asymptomatic infection with the omicron variant, the broader community prevalence during the omicron era, or both.